The Military Balance 2013 : the annual assessent of global military capabilities and defence economics - Hackett, James; International Institute For Strategic Studies (Oxfordshire : Routledge, 2013)
The military balance is a comprehensive and independent assessment of global military capabilities and defence economics. It is also a reference work on developments in global military and security affairs.
Book is accompanied by one Wall chart titled'The 2013 Chart of Conflict.' bearing the same call number and available at Bahagian Koleksi Media.
Keywords: Armed Forces -- Periodicals; Military capital; Military statistics; Military readiness; Military supplies